Education as Reproduction of Hegemony and Its Antihesis - Del Roio, Marcos [UNESP] (My University, 2022)
Gramsci’s was concerned with culture and school from an early age, while he was still in Sardinia. Classical studies and the cultural tradition in the hometown occupied much of young Gramsci’s time, although his relationship with the school was very conflictual and difficult, as it was quite poor and backward and that smothered the development of his taste for natural sciences and arts and crafts.